EQUIVALENCE IN TRANSLATION: A COMPARATIVE STUDY OF ENGLISH-UZBEK LITERARY TEXTS AT ANDIJAN STATE INSTITUTE OF FOREIGN LANGUAGES - Alijonova Gulhayo; Ahmedov Azimjon (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This thesis explores the notion of equivalence in translation within the context of English-Uzbek literary translation. Drawing upon theoretical contributions by scholars such as Eugene Nida, J.C. Catford, and Mona Baker, the study analyzes translated literary texts used in academic programs at Andijan State Institute of Foreign Languages. The research highlights how translators balance fidelity and cultural relevance, particularly in educational contexts.